2015
DOI: 10.1124/jpet.115.227793
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologic Characterization of AMG 334, a Potent and Selective Human Monoclonal Antibody against the Calcitonin Gene-Related Peptide Receptor

Abstract: Therapeutic agents that block the calcitonin gene-related peptide (CGRP) signaling pathway are a highly anticipated and promising new drug class for migraine therapy, especially after reports that small-molecule CGRP-receptor antagonists are efficacious for both acute migraine treatment and migraine prevention. Using XenoMouse technology, we successfully generated AMG 334, a fully human monoclonal antibody against the CGRP receptor. Here we show that AMG 334 competes with [ 125 I]-CGRP binding to the human CGR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
198
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(204 citation statements)
references
References 45 publications
4
198
1
1
Order By: Relevance
“…These include CGRP-binding RNA-Spiegelmers (e.g., NOX-L41 [14]) and monoclonal humanized antibodies directed against CGRP ('nezumabs', for the nomenclature of antibodies, see [15]: ALD403; TEV-48125; LY2951742-galcanezumab) [16][17][18][19]. In addition, a fully human monoclonal antibody ([ 8 _ T D $ D I F F ] AMG 334, erenumab, a 'numab' [15]) has been developed that is targeted against the CGRP receptor [20].…”
Section: Blocking the Cgrp Systemmentioning
confidence: 99%
“…These include CGRP-binding RNA-Spiegelmers (e.g., NOX-L41 [14]) and monoclonal humanized antibodies directed against CGRP ('nezumabs', for the nomenclature of antibodies, see [15]: ALD403; TEV-48125; LY2951742-galcanezumab) [16][17][18][19]. In addition, a fully human monoclonal antibody ([ 8 _ T D $ D I F F ] AMG 334, erenumab, a 'numab' [15]) has been developed that is targeted against the CGRP receptor [20].…”
Section: Blocking the Cgrp Systemmentioning
confidence: 99%
“…The approach to targeting the CGRP receptor was chosen because, as the scientists who developed it, including the lead, Dr. Cen Xu, wrote, “the ligand binding site of CGRP on the calcitonin receptor–like receptor (CRLR)–receptor activity‐modifying protein‐1 (RAMP1) CGRP‐receptor complex is broad; therefore, an antibody that can span the distance between these receptor subunits can offer the most effective blockade; 2) high selectivity for the CGRP receptor complex, which shares similarities with other receptors in the family, and if these other receptors are blocked by a less selective agent, undesired side effects could arise; and 3) the prolonged serum half‐life of an antibody can permit longer dosing intervals, which are ideal for preventive therapies.”…”
Section: Overview Of the Four Monoclonal Antibodiesmentioning
confidence: 99%
“…In vitro data have shown that erenumab binds to human CGRP receptors with high affinity (dissociation equilibrium constant K D  = 20 pM) and potency (IC 50  = 2.3 nM) in a competitive and reversible manner [8]. Results from single-ascending dose (SAD) and multiple-ascending dose (MAD) phase 1 studies (NCT01688739 and NCT01723514, respectively) have been reported and showed that erenumab inhibited CIDBF in healthy and migraine subjects, indicating CGRP-receptor antagonism [9] (de Hoon JN, Van Hecken A, Yan L, Smith B, Chen JS, Bautista E, et al, unpublished data).…”
Section: Introductionmentioning
confidence: 99%